Differentiation of different stages of brain tumor infiltration using optical coherence tomography: Comparison of two systems and histology - Strenge, Paul; Lange, Birgit; Draxinger, Wolfgang; Grill, Christin; Danicke, Veit; Theisen-Kunde, Dirk; Hagel, Christian; Spahr-Hess, Sonja; Bonsanto, Matteo M.; Handels, Heinz; Huber, Robert; Brinkmann, Ralf (Frontiers in Oncology, 2022)
Discrimination of tumour infiltrated tissue from non-tumourous brain tissue during the neurosurgical tumour excision is a major challenge in neurosurgery. It is critical to achieve full tumour removal, since it directly correlates with the survival rate of the patient. Optical coherence tomography (OCT) might be an additional imaging method in the field of neurosurgery, which enables the classification of different levels of tumour infiltration and non-tumourous tissue. This work investigates two OCT systems with different imaging wavelength (930 nm/ 1310 nm) and different resolution (axial(air): 4.9 µm/ 16 µm , lateral: 5.2 µm/ 22 µm) in their ability to identify different levels of tumour infiltration based on freshly excised ex vivo brain samples. For the classification a convolutional neural network was used. For both systems the neural network was able to achieve classification accuracies above 91 % for the discrimination of healthy white matter and highly tumour infiltrated white matter (tumour infiltration >60%). This work shows, that both OCT systems with different optical properties achieve similar results when it comes to the identification of different stages of brain tumour infiltration.